Daño en semillas de Erythrina americana Mill., (Leguminosae: Faboideae: Erythrininae) por el brúquido Specularius impressithorax (Pic, 1932) (Coleoptera: Bruchidae) y su efecto en la germinación - Parra-Gil, Pedro de Jesus; Espinosa-Vásquez, Gonzalo; Lucio-Cruz, Claudia Yarim; Romero-Nápoles, Jesús; Arce-Cervantes, Oscar (Instituto de Ecología, A.C., 2023)
The seeds of Erythrina americana Mill. are consumed by the bruchid Specularius impressithorax. Hence to evaluate the effect that the beetles can have on the sedes, the percentage of damage to E. americana seeds in the pre-dispersal stage was determined, as well as the accumulated damage during one year caused by S. impressithorax. The germination percentage of healthy and damaged seeds were evaluated. The seeds were collected in the Tulancingo Valley, Hidalgo, Mexico in December 2017. 1,272 seeds had been collected from nine different trees, which remained at least 500 m away from each other. The number of holes were counted in the seeds, that is, the number of bruchids that emerged from each seed (n = 269). The average damage percentage during the pre-dispersal of the seeds was 17.4% and for the post-dispersal stage it was 83.1%. Seeds with a bruchid exit hole germinated in 66.6%. The undamaged seeds presented a germination percentage of 2.2%, because the E. americana seeds present dormancy. The percentage of germination of the seeds with an emergency hole caused by S. impressithorax (66.6%), indicates that when an E. americana seed is consumed by a bruchid, it does not damage the embryo, and emulates a natural scarification process.